Strategic Roadmap for 3D‐Printed Reinforcement Using Fused Deposition Modeling: A State‐of‐the Art Review - Mohammad Hematibahar; Roman Fediuk; Komeil Momeni; Makhmud Kharun; Abhijit Bhowmik; Valentin Romanovski (Engineering Reports, 2025)
ABSTRACT With the emergence of 3D‐printing technology, many objects can be manufactured, leading to notable progress in contemporary industrial applications. The present research addresses the original combination of 3‐D printing with reinforcement of concrete and cementitious compounds, especially relating to Fused Deposition Modeling (FDM). The investigation comprehensively covers the effect of the use of various printing materials and reinforcement constructs, and focuses on geometry as an important parameter to adjust the mechanical properties and ductility of the printed materials. Using deep analyses, it has been concluded that FDM becomes a key technology in the 3D‐printing of reinforced concrete and cement members, which permits design optimization of structural performance. The results highlight that the geometrical features of the reinforcement are crucially important to the improvement in flexural strength and energy dissipation. Specifically, auxetic and truss geometries are identified as superior configurations for improving these properties, while alternative patterns can significantly augment the ductility and energy absorption capacity of concrete. The flexural strength of reinforced concrete samples improves when concrete is reinforced with lattice truss, honeycomb, and different types of trusses by 27%, 160%, and 12% respectively. When concrete or cementitious mortar is reinforced with auxetic structure and lattice structure, the compressive strength improves by more than 18.5% and 33.7% respectively. While hyperboloid shell and steel auxetic tube are added to concrete, the compressive strength of concrete decreases by more than 20% and 24% respectively. This study provides insights into the future of 3D‐printed reinforced concrete.